CAFE: an R package for the detection of gross chromosomal abnormalities from gene expression microarray data - Bollen, Sander; Leddin, Mathias; Andrade-Navarro, Miguel A.; Mah, Nancy (Bioinformatics, 2014)
The current methods available to detect chromosomal abnormalities from DNA microarray expression data are cumbersome and inflexible. CAFE has been developed to alleviate these issues. It is implemented as an R package that analyzes Affymetrix *.CEL files and comes with flexible plotting functions, easing visualization of chromosomal abnormalities. Availability and implementation: CAFE is available from https://bitbucket.org/cob87icW6z/cafe/ as both source and compiled packages for Linux and Windows. It is released under the GPL version 3 license. CAFE will also be freely available from Bioconductor. Contact: sander.h.bollen@gmail.com or nancy.mah@mdc-berlin.de Supplementary information: Supplementary data are available at Bioinformatics online.